2009
DOI: 10.1002/pon.1396
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity preferences of ovarian cancer survivors

Abstract: Objective: Regular physical activity is positively associated with quality of life in ovarian cancer survivors, but no data exist on how best to promote activity in this population. This study investigated the interests and preferences of ovarian cancer survivors with regard to physical activity participation.Methods: A provincial, population-based postal survey of ovarian cancer survivors in Alberta, Canada, was performed including measures of self-reported physical activity, medical and demographic variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
97
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 26 publications
14
97
1
1
Order By: Relevance
“…Encouraging home-based exercise is an effective and economic alternative to facility-based training, significantly reducing the requirements and costs for exercise staffing, facility, and equipment 62 . Moreover, the convenience of exercise has been the root of preference on the part of many cancer survivors for homebased exercise 34,35,[41][42][43] . Because concerns about patient adherence to home-based exercise prescription in the absence of direct supervision are valid, the sep has implemented adherence-boosting strategies that are further discussed later in this article.…”
Section: Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraging home-based exercise is an effective and economic alternative to facility-based training, significantly reducing the requirements and costs for exercise staffing, facility, and equipment 62 . Moreover, the convenience of exercise has been the root of preference on the part of many cancer survivors for homebased exercise 34,35,[41][42][43] . Because concerns about patient adherence to home-based exercise prescription in the absence of direct supervision are valid, the sep has implemented adherence-boosting strategies that are further discussed later in this article.…”
Section: Facilitymentioning
confidence: 99%
“…Finally, educational seminars on physical activity for cancer survivors are offered on a monthly basis to improve the understanding of the benefits of an active lifestyle. The foregoing program components accommodate the identified preferences of cancer survivors for access to a multifaceted approach to exercise, including flexibility in structure, social support, print educational material, home-based exercise equipment and instruction, and routine follow-up from the cancer exercise specialists 28,29,31,32,34,37,[40][41][42][43][44]82 .…”
Section: Program Componentsmentioning
confidence: 99%
“…Ve struktuře péče o nemocné dítě s vážným dlouhodobým onemocněním má vedle účinné léčby klíčové místo formování, rozvíjení a podpora celkové pohody (Huberty, Vener, Waltman, Ott, Twiss, Gross, McGuire & Dwyer, 2009;Stevinson, Capstick, Schepansky, Tonkin, Vallance, Ladha, Steed, Faught & Courneya, 2009) • dimenzi fyzickou,…”
Section: úVodunclassified
“…This was highlighted in a study by Courneya et al (2003b) who found that when participants in their study were given a choice of activity, over 95% chose walking. This preference may be dependent on participants' current level of fitness and engagement with physical activity, since Stevinson et al (2009b) found that preference for walking in ovarian cancer survivors was greatest for those survivors who were not currently meeting physical activity guidelines. Nevertheless, walking has been recognised as an achievable form of activity for most cancer survivors regardless of fitness levels or income (which may affect the resources a person has access to).…”
Section: Type Of Activitymentioning
confidence: 99%
“…Some individuals show a strong preference for exercising with other cancer patients, who are of similar fitness levels and understand each other's experiences (Adamsen et al, 2001;Blaney et al, 2010;Turner et al, 2004), while others find no such preference (Karvinen et al, 2006;Stevinson et al, 2009b). Some cancer survivors may also have a preference for exercising individually due to certain side effects of treatment-for example, incontinence amongst prostate and colorectal cancer survivors is likely to result in a strong preference to exercise alone and at home (Blaney et al, 2010).…”
Section: Individual Versus Group Basedmentioning
confidence: 99%